2011
DOI: 10.1111/j.1365-2958.2011.07677.x
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Caulobacter cell division machine

Abstract: Summary Cytokinesis in Gram-negative bacteria is mediated by a multiprotein machine (the divisome) that invaginates and remodels the inner membrane, peptidoglycan, and outer membrane. Understanding the order of divisome assembly would inform models of the interactions among its components and their respective functions. We leveraged the ability to isolate synchronous populations of Caulobacter crescentus cells to investigate assembly of the divisome and place the arrival of each component into functional conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
213
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(224 citation statements)
references
References 75 publications
10
213
0
1
Order By: Relevance
“…A similar pattern is observed in the divisome proteins that are components of the cell-division machine (27). Of 23 divisome proteins, 5 (FzlA, FtsQ, FtsK, FtsL, and FtsB) have this characteristic (worksheet "Divisome Genes" in Dataset S2).…”
Section: Dramatic Cell Cycle-dependent Changes In the Cell's Proteinsupporting
confidence: 59%
“…A similar pattern is observed in the divisome proteins that are components of the cell-division machine (27). Of 23 divisome proteins, 5 (FzlA, FtsQ, FtsK, FtsL, and FtsB) have this characteristic (worksheet "Divisome Genes" in Dataset S2).…”
Section: Dramatic Cell Cycle-dependent Changes In the Cell's Proteinsupporting
confidence: 59%
“…In C. crescentus, early cell-cycle unipolar FtsZ foci have been reported (2), although whether this localization is more than a postdivision remnant of the Z ring has not been resolved. FtsA in C. crescentus, however, is diffuse in the cytoplasm in the first half of the cell cycle, and then localizes to the Z ring until septation is complete (2).…”
Section: Discussionmentioning
confidence: 99%
“…After elongation is complete, divisome proteins assemble at the midcell in a specific temporal order where one component recruits the next via protein-protein interactions. A comprehensive study in the α-proteobacterium Caulobacter crescentus, however, revealed significant differences from the E. coli model in the timing of localization of cell-division proteins and the genetic requirements for localization (2).…”
mentioning
confidence: 98%
“…It is expected that the process will be significantly different among microbes: many subunits are not ubiquitously conserved, cytoskeletal elements can vary in structure and function (14), recruitment hierarchy is different even in organisms with conserved subunits (15), and niche-specific regulators of PG growth and interchangeability of enzymatic components seem to be prevalent (4,10). Mapping the differences and also linking them to the physiology of diverse organisms will be in the core of future studies in the field and will help us dissect the general underlying principles of these machineries from the nichespecific ones.…”
mentioning
confidence: 99%